Pelas ruas de Maringá : arborização de acompanhamento viário e os parâmetros de uso e ocupação do solo - Albertin, Ricardo Massulo (2016)
The street arborization is an important component of urban infrastructure and public healthcare in towns. The afforestation project along with urban planning, would allow a healthier environment, and with that, the redution of negative impacts, for the trees as well as for its surroundings. In this context, the main objective of this research was to study the relation between the parameters of use an occupation of the soil as well as the street arborization afforestation in the city of Maringa, Parana, Brazil. This way, it was tried to relate the street arborization afforestation with the urbanistic parameters of use and occupation of the soil, such as: location, chracteristics of the land, quantitative and qualitative characteristics of the buildings, awnings and facades, different ways and power lines. The areas to be studied were defined according to the Use and Occupation of the Soil Law in three distinct areas: residential zone (ZR2), commercial zone (ZCC) and special zone (ZE1). For the field research, a drawn spreadsheet was structured from two lines: parameters of soil occupation and street arborization afforestation. The Total census survey was adopted, which means, all the trees individuals and the soil occupation parameters where trees are found were evaluated. A method was developed, which allows 52 parameters, out of which 25 related to the use and occupation of the soil and 27 for the street arborization afforestation. With this, it was possible to determine the degree of compatibility of the trees with its use and occupation. The results allowed the tree to be related to the parameters of use and occupation of the soil. In the ZCC, a great diversity of buildings could be seen as a result of an old area estabilished in the city planning. In the ZE1 and ZR2 a padronization of buildings could be seen, given the relatively recent urban occupation which happened in 2006 and 2011, respectively. In ZR2 the option of planting medium sized trees, which width was compatible with the pavement and streets, and mainly the Front recess requirements, showed correspondence with the parameters of use and occupation of the soil. Particularly in ZE1, despite the fact that the trees corresponded the parameters, the home base of the buildings may, in the future, show incompatibility with the aperture of the white ipês treetops. Finally, we can conclude that the compatibility of the street afforestation with the parameters of use and occupation of soil defended in this thesis will result in a more efficient management which will reduce the negative impacts to the buildings and to passerby. In this sense, it is necessary to articulate the connection between ecological systems and social systems, trying to make the street afforestation compatible with the parameters of use and occupation of the soil.